Remote Learning and Foregoing the Dream - Kotok, Stephen (Journal of Interdisciplinary Studies in Education, 2021)
Due to Covid-19, almost all public-school districts across the U.S. suspended in-person learning and shifted overnight to remote learning. I am writing this in May of 2020. The future of the pandemic is unclear. However, we need to think critically how this challenging time informs post-Covid educational policies and curriculum.